The Relationship between Family Stress and Internet Dependence: The Mediating Role of Loneliness—Empirical Analysis Based on CGSS2017 - Kaibiao Xiang; Huilin Song; Zhenmin Cheng (Discrete Dynamics in Nature and Society)
With the explosive development of modern technology, Internet dependence has become an important hindrance to normal use of the Internet. The influence of the family environment and individual perception has gradually emerged in practice, while the theoretical research is still insufficient yet. Therefore, to clarify the specific influence mechanism between them, we divided family stress into two dimensions in this study, which are behavioral stress and emotional stress. Furthermore, combined with individual loneliness, a theoretical framework of the mediating effect is constructed to confirm the influence of family stress on Internet dependence and explore its action path and mechanism. Based on the data of CGSS2017, the empirical research shows that both behavioral and emotional stress from family can significantly increase the degree of Internet dependence of individuals and individual loneliness plays a partial mediating role between family stress and degree of Internet dependence. The results of this study provide powerful theoretical proof for practical experience and also provide a possible way of solving problems with Internet dependence in practice.